2020
DOI: 10.1111/jnc.14947
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal electronic cigarette exposure decreases brain glucose utilization and worsens outcome in offspring hypoxic–ischemic brain injury

Abstract: It has been shown that prenatal nicotine and tobacco smoke exposure can cause different neurobehavioral disorders in the offspring. We hypothesize that prenatal exposure to nicotine‐containing electronic cigarette (e‐Cig) vapor can predispose newborn to enhanced sensitivity to hypoxic–ischemic (HI) brain injury and impaired motor and cognitive functions. In this study, pregnant CD1 mice were exposed to e‐Cig vapor (2.4% nicotine). Primary cortical neurons isolated from e‐Cig exposed fetus were exposed to oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
15

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 72 publications
(126 reference statements)
0
29
0
15
Order By: Relevance
“…An altogether decreased neuronal metabolism was noted. This became evident by a reduction in glucose uptake, expression of glucose transporters, adenosine triphosphate content, as well as a lower mitochondrial membrane potential 22 . E-cigarette exposure also led to reduced cell viability and increased DNA damage 22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An altogether decreased neuronal metabolism was noted. This became evident by a reduction in glucose uptake, expression of glucose transporters, adenosine triphosphate content, as well as a lower mitochondrial membrane potential 22 . E-cigarette exposure also led to reduced cell viability and increased DNA damage 22 .…”
Section: Discussionmentioning
confidence: 99%
“…This became evident by a reduction in glucose uptake, expression of glucose transporters, adenosine triphosphate content, as well as a lower mitochondrial membrane potential 22 . E-cigarette exposure also led to reduced cell viability and increased DNA damage 22 . In addition, the researchers found increased sensitivity of the mice to postnatal hypoxic-ischaemic brain injury caused by prenatal exposure to +Nic e-cigarettes, which is also seen in neonates with inadequate oxygen supply.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it may facilitate the onset of stroke and worsen the condition of post-ischemic brain injury [75]. Another recent study also reported that e-cigarette vaping may decrease neuronal glucose utilization, which could result in increased risk for ischemic brain injury and stroke [135]. Recently, McAlinden et al suggested that, nicotine-based e-cigarettes or vaping may contribute to the upregulation of ACE2 which may also play an important role in progression and outcome of COVID-19 [136].…”
Section: Vaping (E-cigarette) Covid-19 and Cerebrovascular-neurologmentioning
confidence: 99%